Antibiotic prophylaxis in alimentary tract surgery - Chaber, Andrzej (Contemporary Oncology/Współczesna Onkologia, 1999)
Postoperative infections are an important cause of morbidity, mortality and prolonged hospital stay. Effective antibiotic prophylaxis can reduce the incidence of postoperative infections and be cost-effective. It is essential for patients at high risk of developing postoperative complications, because of either the nature of the operation or individual factors. It should be directed against the most likely infecting organisms; the potential pathogens vary with the type of operation. The spectrum of antibacterial activity of cephalosporins and amoxycillin-clavulanic acid, which covers major Gram-negative and Gram-positive pathogens, makes them ideally suited for surgical prophylaxis. Monotherapy with a single dose of antibiotic is the most cost-effective regimen for surgical prophylaxis.